Robust scalable high throughput production of monodisperse drops. Issue 21 (29th September 2016) - Amstad, E.; Chemama, M.; Eggersdorfer, M.; Arriaga, L. R.; Brenner, M. P.; Weitz, D. A.
Abstract : We present a microfluidic device, a millipede device, that contains 550 nozzles and enables high thoughput production of monodisperse drops. Abstract : Monodisperse drops with diameters between 20 μm and 200 μm can be used to produce particles or capsules for many applications such as for cosmetics, food, and biotechnology. Drops composed of low viscosity fluids can be conveniently made using microfluidic devices. However, the throughput of microfluidic devices is limited and scale-up, achieved by increasing the number of devices run in parallel, can compromise the narrow drop-size distribution. In this paper, we present a microfluidic device, the millipede device, which forms drops through a static instability such that the fluid volume that is pinched off is the same every time a drop forms. As a result, the drops are highly monodisperse because their size is solely determined by the device geometry. This makes the operation of the device very robust. Therefore, the device can be scaled to a large number of nozzles operating simultaneously on the same chip; we demonstrate the operation of more than 500 nozzles on a single chip that produces up to 150 mL h −1 of highly monodisperse drops.